Cu-Zn disorder in Cu2ZnGeSe4: A complementary neutron diffraction and Raman spectroscopy study. (December 2016) - Gurieva, G.; Többens, D.M.; Valakh, M. Ya.; Schorr, S.
Abstract: The crystal structure of the quaternary compound semiconductor Cu2 ZnGeSe4 (CZGSe) was investigated by the complementary use of neutron diffraction, and Raman spectroscopy. The powder sample, which resulting from wavelength dispersive X-ray spectroscopy (WDX) turned out to be single phase Cu-rich CZGSe, was synthesized by solid state reaction of the pure elements in an evacuated silica tube at 700 °C. Raman spectroscopy confirmed the homogeneity and phase purity of the sample, in addition, the kesterite type structure was suggested. Rietveld analysis of the neutron diffraction data confirmed that the compound crystallizes in the tetragonal kesterite type structure. The refined site occupancy factors were used to determine the average neutron scattering lengths of the cation sites, giving insights into cation distribution and finally point defect types. Thus it has been shown, that additional to the CuZn -ZnCu anti-site defects in the lattice planes at z =¼ and ¾ (Cu-Zn disorder) also the off-stoichiometry type related point defects like Cui and CuZn occur in Cu-rich CZGSe. Highlights: Cu2 ZnGeSe4 (CZGSe) was investigated by neutron diffraction. Cu-rich CZGSe shows Cui and CuZn point defects additional to the CuZn -ZnCu anti-site defects. The concentration of these defects has been calculated.